Relationship between Burnout Syndrome and Job Performance in Secondary Education Teachers. (LACCEI, 2024)
Emotional health in the development of the human being plays a very important role because the result of their daily and work activities depends on it, in this context, the present research aims to determine the relationship between burnout syndrome and work performance in teachers of the José Carlos Mariátegui school, Pomacochas - Amazonas, 2021. The research is of non-experimental design and the hypothetical inductive-deductive method was used and the type of study was descriptive-correlational with a quantitative approach, the finite sample consisted of 30 teachers the instruments used to evaluate the population were the Maslach Burnout Inventory test and the Work Performance Questionnaire, both elaborated based on the standards established in the Likert scale. The variables were correlated with Pearson's test through the SPSS program in its latest version Statistics 28.0.1, the results describe a negative inverse relationship, i.e. the lower the burnout syndrome the higher the job performance, there being no significant relationship between the two variables, it is concluded that, despite having burnout syndrome, Mariateguistas teachers have a good job performance due to the demands of the school and their self-motivation.